2020
DOI: 10.51983/ajeat-2020.9.1.1081
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Emerging Methods and Ways in Agricultural Sciences: With Reference to Organic Farming

Abstract: Agricultural Sciences is an Applied Science but has its touch with social science due to its nature. It uses various kinds of tools, techniques, procedure, methods, principles of science; that is responsible for the cultivation of plants, crops, vegetables, livestock as well as animals. Agriculture is dedicated to the sedentary human civilization and by this people can meet their food demand. As far as the history of agriculture it is noted that agriculture as a concept emerged thousands of years before about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It was found that the quality of information has a positive relationship when the workplace environment is also of high quality. In a similar way, it was identified by Paul et al (2018) that there is a positive association between quality of information and organisational performance. It was argued by Davis (2014) that the relationship between organisational impact and the quality of systems in place is mediated by the quality of information.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 64%
“…It was found that the quality of information has a positive relationship when the workplace environment is also of high quality. In a similar way, it was identified by Paul et al (2018) that there is a positive association between quality of information and organisational performance. It was argued by Davis (2014) that the relationship between organisational impact and the quality of systems in place is mediated by the quality of information.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 64%